The North American Layman's Understanding of COVID-19: Are We Doing Enough? - Ali Salimi; Hassan ElHawary; Nermin Diab; Lee Smith (Frontiers Media S.A., 2020)
Background: In the absence of an effective vaccine, public health policies are aimed at awareness, and education of the general public in order to contain the quickly spreading COVID-19 pandemic. Most of the recommended precautionary measures are dependent on human behaviors and therefore their effectiveness largely depends on peoples' perception and attitudes toward the disease. This study aimed to assess the level of knowledge, risk perception, and precautionary measures taken in response to COVID-19 in North America.Methods: In this cross-sectional observational study, an online survey targeted to North Americans focused on the public's knowledge of COVID-19, risk perception, and precautionary behaviors taken in response to this pandemic. Descriptive analyses were performed for the whole population and the subgroup analyses contrasted the differences between Americans and Canadians.Results: The cohort comprised 1,264 relatively young participants with an average age of 28.6 ± 9.8 years. The vast majority (>90%) were knowledgeable about COVID-19. Regarding risk perception, about a quarter assumed to be at less risk to contract the disease, and 42.8% considered themselves to be less contagious than others. While the vast majority avoided performing risky behaviors, only a small proportion (13.2%) wore a face mask-which is in line with the public health recommendations of the two countries at the time of data collection. Overall, a larger proportion of Canadian participants (55.8%) were satisfied with the performance of their national public health in response to the current pandemic, compared to their American counterparts (12.2%).Discussion: Data regarding the public's knowledge of COVID-19, risk perception, and behaviors in response to this pandemic is limited. The results of this study highlight that this relatively young and educated sample of North Americans had a high level of knowledge about COVID-19 and a large proportion of them were taking the precautionary measures against this pandemic. However, a significant number of individuals believe to be at less risk of contracting the disease compared to the general population. Educating the public that no one is safe from this disease, could play a role in further limiting risky behaviors and ultimately facilitating disease containment.